2005
DOI: 10.1002/ptr.1621
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of LPS‐induced central and peripheral hyperalgesia by green tea extract

Abstract: Tea has recently attracted a great deal of attention for its beneficial health effects. Green tea polyphenols inhibit the production of arachidonic acid metabolites and leukotrienes resulting in decreased inflammatory responses. In the present study, the effect of green tea extract (GTE) on lipopolysaccharide (LPS)-induced thermal and behavioural hyperalgesia in mice and the possible involvement of the cyclooxygenase pathway in this paradigm was evaluated. GTE (25 mg/kg, i.p.), nimesulide (2 mg/kg, i.p.) and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…[40] suggested that EGCG exerts anxiolytic effect by interacting with GABA receptors, and Kaur et al. [28] also found that green tea extract attenuates LPS‐induced central and peripheral hyperalgesia by selective inhibition of cyclooxygenase‐2 enzyme. In our study, we also found a significant impairment in memory of fatigued mice in elevated plus maze and this finding is supported by the results of Haiq‐Ferquson et al.…”
Section: Discussionmentioning
confidence: 99%
“…[40] suggested that EGCG exerts anxiolytic effect by interacting with GABA receptors, and Kaur et al. [28] also found that green tea extract attenuates LPS‐induced central and peripheral hyperalgesia by selective inhibition of cyclooxygenase‐2 enzyme. In our study, we also found a significant impairment in memory of fatigued mice in elevated plus maze and this finding is supported by the results of Haiq‐Ferquson et al.…”
Section: Discussionmentioning
confidence: 99%
“…Stress‐induced hyperalgesia was assessed by tail‐immersion test. Mice were held individually and their tails were immersed in hot water (52.5 ± 0.5 °C) for not more than 10 s as cut off time, and withdrawal latency was observed on the same days as the immobility was observed [21].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have demonstrated an antinociceptive effect of green tea extract on inflammatory and neuropathic pain [1,2]. (−)-Epigallocatechin-3-gallate (EGCG) is one of the major catechins of green tea leaves and it has been shown to exhibit analgesic efficacy.…”
Section: Introductionmentioning
confidence: 99%